Development of optical microneedle–lens array for photodynamic therapy. - Park, Jongho; Zhang, Jingzong; Kim, Beomjoon (Biomedical Microdevices, 2025)
Recently, photodynamic therapy (PDT) which involves a photosensitizer (PS), a special drug activated by light, and light irradiation has been widely used in treating various skin diseases such as port-wine stain as well as cancers such as melanoma and non-melanoma skin cancers. PDT comprises two general steps: the introduction of PS into the body or a specific spot to be treated, and the irradiation process using a light source with a specific wavelength to excite the PS. Although PDT is gaining great attention owing to its potential as a targeted approach in the treatment of skin cancers, several limitations still exist for practical use. One of the biggest challenges is the limited penetration of light owing to scattering, reflection, and absorption of light inside the skin layers. In addition, accidental light exposure of the target area causes additional cellular damage, which causes unexpected complications. To solve these issues, we introduced an optical microneedle–lens array (OMLA) to improve the efficiency and safety of PDT treatment. We designed and fabricated a novel optical microneedle–lens array with controlled dimensions to optimize light transmission. In addition, PS was coated uniformly over the tips of the OMLA using the dip coating method. Finally, we confirmed that the PS coated on the OMLA was released into the target area and subsequently generated radical oxygen by light irradiation. We expect that our proposed OMLA for PDT treatment can realize a new light-transmission platform optimized for PDT with targeting various types of skin cancers.